2013
DOI: 10.1186/1471-2180-13-37
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide substitutions in dengue virus serotypes from Asian and American countries: insights into intracodon recombination and purifying selection

Abstract: BackgroundDengue virus (DENV) infection represents a significant public health problem in many subtropical and tropical countries. Although genetically closely related, the four serotypes of DENV differ in antigenicity for which cross protection among serotypes is limited. It is also believed that both multi-serotype infection as well as the evolution of viral antigenicity may have confounding effects in increased dengue epidemics. Numerous studies have been performed that investigated genetic diversity of DEN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 45 publications
2
20
0
3
Order By: Relevance
“…As a result, several mutations previously incorporated in a genomic region can be transferred simultaneously to another region by a single recombination event. Interestingly, at the codon level, recombination can also alter the codon state by intra-codon recombination events (Arenas and Posada, 2010a), a process observed in viruses (Behura and Severson, 2013). Nevertheless, the fate of these genetic changes will be ultimately determined by natural selection and genetic drift.…”
Section: The Impact Of Recombinationmentioning
confidence: 99%
“…As a result, several mutations previously incorporated in a genomic region can be transferred simultaneously to another region by a single recombination event. Interestingly, at the codon level, recombination can also alter the codon state by intra-codon recombination events (Arenas and Posada, 2010a), a process observed in viruses (Behura and Severson, 2013). Nevertheless, the fate of these genetic changes will be ultimately determined by natural selection and genetic drift.…”
Section: The Impact Of Recombinationmentioning
confidence: 99%
“…Our recent studies have revealed genome-wide differential usage of codon sequences in different insect species including A. aegypti (Behura and Severson 2012b). In addition to that, we have also shown that codon bias is a significant factor in genetic diversity of DENV populations (Behura and Severson 2013b). Specifically, codon usage bias is known to have an association with translational efficiency and/or accuracy (Rocha 2006; Behura and Severson 2011; Rodriguez et al 2012; Novoa et al 2012) as well as expression levels of protein coding genes (Akashi 2001; Najafabadi and Salavati 2008; Najafabadi et al 2009; Camiolo et al 2012).…”
Section: Introductionmentioning
confidence: 71%
“…Further, as DENV is dependent on the host translational apparatus, we and others have reported that DENV isolates show significant biases in synonymous codon usage that are consistent with their geographic origin and likely result from adaptive interaction with the mosquito and human hosts [109,119,120]. We also observed that codon context (the propensity of adjacent codons to consistently pair with themselves or another codon) among Asian and American DENV isolates showed a bias toward (A)(A/T)(A)-(A)(A/T)(A) coding sequences and general avoidance of (C/G)(C/A)(C/G)-(C/G)(C/A)(C/G) coding sequences across all four serotypes [119].…”
Section: Genome Coevolution and Vector Competencementioning
confidence: 84%
“…We also observed that codon context (the propensity of adjacent codons to consistently pair with themselves or another codon) among Asian and American DENV isolates showed a bias toward (A)(A/T)(A)-(A)(A/T)(A) coding sequences and general avoidance of (C/G)(C/A)(C/G)-(C/G)(C/A)(C/G) coding sequences across all four serotypes [119]. In addition to DENV, we also compared [121] the codon context bias of other flaviviruses, including West Nile virus (WNV) and yellow fever virus (YFV), and determined that codon context bias varies in a bicluster manner with A. aegypti genes that have been shown to be differentially expressed following infection by these viruses [92].…”
Section: Genome Coevolution and Vector Competencementioning
confidence: 99%